The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/nu14245384
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine Intake throughout Pregnancy, and Factors Associated with Non-Compliance with Recommendations: A Cohort Study

Abstract: Maternal caffeine consumption is associated with adverse gestational outcomes. The aim of this study was to assess the intake of caffeine and factors associated with the non-adherence to caffeine intake recommendations in a cohort of 463 women before (T0) and in each trimester of gestation (T1, T2, and T3), by using validated questionnaires. Caffeine intake (median (mg/day), IQR) was 100.0 (181.1) at T0, 9.42 (66.2) at T1, 12.5 (65.6) at T2, and 14.0 (61.1) at T3 (p < 0.001). Non-compliance prevalence (inta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…However, this ′safe′ dosage is being reevaluated based on increasing evidence, which has shown that even daily doses of less than 300 mg may increase the risk of pregnancy failure. Furthermore, other studies found that even a daily intake as low as 100–200 mg during pregnancy is associated with an increased risk of miscarriage, fetal growth restriction, low birth weight, as well as increased risks to the offspring, including cognitive development impairments, overweight, and obesity [ 182 ]. These studies raise concern that there may be no absolute safe threshold of caffeine consumption during pregnancy.…”
Section: Should Pregnant Women Avoid Caffeine?mentioning
confidence: 99%
“…However, this ′safe′ dosage is being reevaluated based on increasing evidence, which has shown that even daily doses of less than 300 mg may increase the risk of pregnancy failure. Furthermore, other studies found that even a daily intake as low as 100–200 mg during pregnancy is associated with an increased risk of miscarriage, fetal growth restriction, low birth weight, as well as increased risks to the offspring, including cognitive development impairments, overweight, and obesity [ 182 ]. These studies raise concern that there may be no absolute safe threshold of caffeine consumption during pregnancy.…”
Section: Should Pregnant Women Avoid Caffeine?mentioning
confidence: 99%